Climate Change in Jordan: A Case Study of Rajeb Basin (Iraqi National Journal of Earth Science (INJES), 2026)
Rajeb Basin is one of the most important basins in Ajloun Governorate in Jordan. This study aims to assess the effect of climate change on the Rajeb basin using the software of the climate indices (Rclimdex) model for three rainfall stations and three meteorological stations. The future impact of climate change is determined using the statistical downscaling model (SDSM) and the second-generation model for the Earth System (CanESM2) for different emission scenarios. Additionally, the study aims to predict the potential future impact of climate change on the flow of the Rajeb basin at the end of the current century using the Soil and Water Assessment Tool (SWAT) model. Regarding temperature, the results show a significant trend for 9 out of 16 extreme indices for all stations. The hot days increased by 12 days between 1982-2020, and the hot nights increased by 10 nights for the same period. The cool days decreased by 15 days between 1982-2020, and the cool nights decreased by 17 nights for the same period. The summer days (Tmax>25℃) increased by 26 days, and the tropical nights (Tmin>20℃) increased by 61 nights for the same period. It is predicted that the temperature will increase 2100 by 0.2℃, 0.57℃, and 1.4℃ based on RCP 2.6, 4.5, and 8.5 scenarios, respectively. The precipitation is predicted to decrease 2100 by 10.8%, 23%, and 43%, for the three scenarios, respectively. Regarding the expected streamflow, SWAT forecast results indicate a decrease in streamflow by 8.1%, 38%, and 69.2% between 2018- 2100 based on RCP 2.6, 4.5, and 8.5, respectively. According to the study, local organizations and decision-makers need to take into consideration the effects of climate change on the Rajeb basin. Pumping operations from the basin must be monitored to ensure the sustainability of water resources.
Keywords: Climate Change, Jordan, Rajeb Basin, SDSM, SWAT, RCPs